(untitled) (Patan Pragya, 2022)
Human agency has an enormous capacity to transform individual livelihood strategies as well as cultivate positive attitudes, collective action, and hope for the betterment of the whole community. In this paper, we argue that ’Musahars agency’ (ability to act in spite of constraints) acts as catalyst for the increment of educational status of the community and school education on the other round cultivate dynamic person for a range of social transformation. The ex-Haruwa-Charuwa and educated youths have been conducting a series of educational campaigns including school establishment. Their campaigns succeeded in terms of awareness-raising, decreasing self-humiliation, and inculcating hope for betterment among the Musahars. Because of political-economic and caste-based marginalization, they were deprived as well as denied educational access. Few of them struggled to gain a school education and their constraints strengthen their capacity to speak out, mobilize and act collectively. The paper tried to explain the formation and mobilization of the Musahar agency for the collective empowerment of the community. We employed participatory observation, key informant interviews, and case study methods to collect information. In spite of structural constraints, poverty, and caste-based discrimination, the Musahar youths and activists succeeded to cultivate educational optimism. A separate school for the Dalits was established to attract all the Dalits into school education. Their campaigns were recognized when a large number of the Musahar students passed school-level education. Their agentive acts are lessons for the marginalized communities to transform education as well as political-economic activities and social well-being.